Spain : Financial Sector Assessment Program-Technical Note-Insurance Sector Supervision and Regulation. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain in the areas of insurance sector supervision and regulation. The Spanish insurance market is complex owing to the presence of large numbers of insurance groups. The supervisory culture in the Directorate General of Insurance and Pension Funds (DGSFP) appears to be reactive or compliance focused. The supervisory focus should shift toward qualitative as well as quantitative review of the insurer's key methods and assumptions, including the proportionate verification of technical provisions and capital requirements. The DGSFP should also develop areas that are now relevant in the Solvency II framework, such as governance and risk management.